+0  
 
0
72
1
avatar

Let f(x) = 3x - 8 and g(f(x)) = 2x^2 - 5x + 3.  Find g(5).

 Jun 7, 2021

Best Answer 

 #1
avatar+2193 
+2

f(x) = 5

3x - 8 = 5

3x = 13

x = 13/3

 

g(f(x)) = 2x^2 - 5x + 3

g(f(13/3)) = 2(13/3)^2 - 5(13/3) + 3

g(f(13/3)) = 2(13/3)^2 - 5(13/3) + 3

g(5) = 2(13/3)^2 - 5(13/3) + 3

Can you take it from here?

 

=^._.^=

 Jun 7, 2021
 #1
avatar+2193 
+2
Best Answer

f(x) = 5

3x - 8 = 5

3x = 13

x = 13/3

 

g(f(x)) = 2x^2 - 5x + 3

g(f(13/3)) = 2(13/3)^2 - 5(13/3) + 3

g(f(13/3)) = 2(13/3)^2 - 5(13/3) + 3

g(5) = 2(13/3)^2 - 5(13/3) + 3

Can you take it from here?

 

=^._.^=

catmg Jun 7, 2021

43 Online Users

avatar